Partial fads2 Gene Knockout Diverts LC-PUFA Biosynthesis via an Alternative Δ8 Pathway with an Impact on the Reproduction of Female Zebrafish (Danio rerio) - Bláhová, Zuzana; Franěk, Roman; Let, Marek; Bláha, Martin; Pšenička, Martin; Mráz, Jan (Genes, 2022)
The zebrafish (Danio rerio) genome contains a single gene fads2 encoding a desaturase (FADS2) with both Δ6 and Δ5 activities, the key player in the endogenous biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs), which serve essential functions as membrane components, sources of energy and signaling molecules. LC-PUFAs include the precursors of eicosanoids and are thus predicted to be indispensable molecules for reproductive health in virtually all vertebrates. In mice, an amniotic vertebrate, fads2 deletion mutants, both males and females, have been confirmed to be sterile. In anamniotic vertebrates, such as fish, there is still no information available on the reproductive (in)ability of fads2 mutants, although zebrafish have become an increasingly important model of lipid metabolism, including some aspects of the generation of germ cells and early embryonic development. In the present study, we apply the CRISPR/Cas9 genome editing system to induce mutations in the zebrafish genome and create crispants displaying a degree of fads2 gene editing within the range of 50-80%. Focusing on adult G0 crispant females, we investigated the LC-PUFA profiles of eggs. Our data suggest an impaired pathway of the LC-PUFA biosynthesis of the ω6 and ω3 series in the first-rate limiting steps of the conversion of linoleic acid (LA) into γ-linolenic acid (GLA), and α-linolenic acid (ALA) into stearidonic acid (SDA), respectively, finally resulting in bad-quality eggs. Our data suggest the existence of an alternative Δ8 pathway, which bypasses the first endogenous LC-PUFA biosynthetic step in zebrafish in vivo, and suggest that the zebrafish bifunctional FADS2 enzyme is actually a trifunctional Δ6/Δ5/Δ8 desaturase.
Keywords: long-chain polyunsaturated (LC-PUFAs) biosynthesis; Reproduction; fads2; rozmnožování; genový knockout; CRISPR/Cas9; Female; dánio pruhované; Gene Knockout Techniques; zvířata; myši; zebrafish (Danio rerio) reproduction; Δ6/Δ5/Δ8 desaturase; Mice; myši knockoutované; desaturasy mastných kyselin; mastné kyseliny; Zebrafish; ženské pohlaví; Male; Mice, Knockout; Fatty Acid Desaturases; Animals; mužské pohlaví; dihomo γ-linolenic acid (DGLA); Fatty Acids